El Q’apachi para Proteger los Cultivos Agropecuarios ante la Caída de Granizadas y Heladas en la Comunidad Campesina de Tuntuma, Distrito de Velille, Provincia de Chumbivilcas – Cusco - Churata Orihuela, Tonicer Santos (2024)
In the high Andean areas of the Cusco region and other departments, farmers are constantly concerned about the threats of climatic phenomena, such as hailstorms and frosts. However, for many decadesthe population managed to obtain satisfactory harvests, leading us to question: if there is or do they have any ancestral cultural element that is in force, referring to the protection of agricultural crops against the threat of hail and frost? How do farmers insure their harvest amid the frequent threat of hail and frost? Indeed, the population has a cultural element and they apply the Q’apachi to control hail and soften the frost, linked to religious deities. In the Peasant Community of Tuntuma, the cultural practice called Q’apachi is in force, the use of which is aimed at controlling the fall of hailstorms and moderates the effects of frost, with the institutionality of the communal organization and/or being a mandatory condition. sectorial and/or parcel drivers involved, strictly fulfilling their roles and functions, practicing cooperation. Without this condition, the late application of Q’apachi does not have any favorable effect. The practice of Q’apachi is a cultural heritage transmitted from generation to generation. Decades ago, the Q’apachi was discovered by the families of the ayllus and, currently, it continues to be practiced in peasant communities to respond in a timely manner to natural phenomena. Even, in the case of hailstorms, the use of firecrackers as emergency support has been incorporated.